2019
DOI: 10.1186/s12978-019-0843-1
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of isolation during facility births in Haiti - a qualitative study

Abstract: BackgroundHaiti’s maternal mortality, stillbirth, and neonatal mortality rates are the highest in Latin America and the Caribbean. Despite inherent risks, the majority of women still deliver at home without supervision from a skilled birth attendant. The purpose of this study was to elucidate factors driving this decision.MethodsWe conducted six focus group discussions with women living in urban (N = 14) or rural (N = 17) areas and asked them questions pertaining to their reasons for delivering at a facility o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…Women who have had more than 5 prenatal visits, whether regular or not, most often give birth in healthcare facility (OR=3.32; p=0.009; 95% CI) (Tab -------------0.00 0.00 0.02 0.00 0.00 ------------- show that, on the contrary, older women are more likely to give birth at home, unlike younger women who give birth in hospital [8]. The marital status of women does not influence the choice of delivery place (p=0.75 at home; p=0.30 at healthcare facility) which corroborates the findings of other studies [7], [8]. The number of pregnancies and / or previous deliveries has no effect on the place of delivery; Primiparous, multiparous and grand multiparas give birth both in hospital and at home.…”
Section: Reasons For Selection Of Place Of Deliverysupporting
confidence: 82%
See 1 more Smart Citation
“…Women who have had more than 5 prenatal visits, whether regular or not, most often give birth in healthcare facility (OR=3.32; p=0.009; 95% CI) (Tab -------------0.00 0.00 0.02 0.00 0.00 ------------- show that, on the contrary, older women are more likely to give birth at home, unlike younger women who give birth in hospital [8]. The marital status of women does not influence the choice of delivery place (p=0.75 at home; p=0.30 at healthcare facility) which corroborates the findings of other studies [7], [8]. The number of pregnancies and / or previous deliveries has no effect on the place of delivery; Primiparous, multiparous and grand multiparas give birth both in hospital and at home.…”
Section: Reasons For Selection Of Place Of Deliverysupporting
confidence: 82%
“…Thus we were able to find that in the tertiary sector of activity, the probability for these women to give birth at home was lower compared to other sectors of economic activity; it positively influences childbirth in hospital (OR = 1.32, p= 0.004). studies have shown that women's economic health quintile plays a role in the birthplace [7,8]. n this study, women are more likely to give birth at home if they are far from the health center, and this risk increases even more if there is no transport available.…”
Section: Reasons For Selection Of Place Of Deliverymentioning
confidence: 64%
“…These same themes have been reported in Haiti and in sub-Saharan Africa. 28 29 Together, these findings point to the possibility that the presence of the matron in the delivery room alongside midwives may facilitate increased comfort and support for women and discourage the mistreatment of women in pain. Midwives could also serve as a resource on biomedical approaches for matrons, thus mitigating the potential for harms related to traditional birth practices.…”
Section: Discussionmentioning
confidence: 95%
“…For example, women place value upon being listened to and being placed at the centre of decision-making processes (Heatley et al 2015;Mei et al 2015;Miron-Shatz and Konheim-Kalkstein 2020). Quality and amount of support provided by midwives and allied health care professionals plays a vital role in level of 'birth satisfaction' reported (Luegmair et al 2018;Dev et al 2019;Miron-Shatz and Konheim-Kalkstein 2020), with women testifying that they feel more positive about their birth experience when their needs and comforts are considered (Luegmair et al 2018;Hall et al 2020).…”
Section: What Is Birth Satisfaction ?mentioning
confidence: 99%